Perencanaan Struktur Jembatan Gantung Ateh Koto pada Nagari Sungai Rimbang Kecamatan Suliki Kabupaten Lima Puluh Kota - 'Abdan Syakuro; Fajri Yusmar; Annisa Prita Melinda; Putri Fauziahtul Asri (Jurnal Sains Dan Teknologi | E-ISSN : 3063-9980, 2026)
The hilly topography of Suliki District, crossed by several rivers, makes bridges a vital infrastructure for community mobility and economic activity, particularly in Nagari Sungai Rimbang. The Ateh Koto suspension bridge in this nagari was damaged by the flooding of the Batang Sinamar River in November 2025, which caused foundation scouring and bank erosion on both abutment sides, altering the bridge span and rendering the structure unsafe for use. This study aims to design a new 50-meter suspension bridge structure that is safe and complies with applicable technical standards. The design was carried out based on topographic and hydrological survey data, with load analysis referring to SNI 1725:2016 and Circular Letter of the Minister of PUPR No. 02/SE/M/2010. The Flood Water Level was determined through hydrological analysis (Log Pearson III method) and hydraulic analysis (Manning's equation), while structural modeling was performed using SAP2000 software to obtain internal forces, stresses, deflections, and dynamic responses of the main cable, hangers, towers, backstay cables, and girders. The results show a 25-year design flood discharge of 328.17 m³/s with a flood water level rise of 2.25 m above normal water level. All upper structure elements satisfy strength requirements with stress ratios below 1.0, maximum deflection of 0.18 m remains below the 0.25 m allowable limit, and the structure's natural frequency of 0.233 Hz lies outside the resonance danger zone (0.5–1.2 Hz), confirming the design is structurally safe and feasible to restore accessibility for the community of Nagari Sungai Rimbang.